Differential association of metabolic syndrome and low-density lipoprotein cholesterol with incident cardiovascular disease according to sex among Koreans: a national population-based study: Population level factors. (18th December 2020) - Kim, Su Yong; Go, Tae-Hwa; Lee, Jun Hyeok; Moon, Jin Sil; Kang, Dae Ryong; Bae, Se Jin; Kim, Se-Eun; Lee, Sang Jun; Cho, Dong-Hyuk; Park, Young Jun; Youn, Young Jin; Kim, Jang Young; et al.
Abstract: Aims: To investigate sex differences in the association of metabolic syndrome (MetS) and/or low-density lipoprotein cholesterol (LDL-C) with the incidence of cardiovascular and cerebrovascular disease (CCVD). Methods and results: A total of 4 702 458 individuals, aged between 40 and 70, without a previous diagnosis of CCVD, underwent at least two health screenings between 2009 and 2011. Of them, 4 193 878 individuals (48.6% women) fulfilled the study requirements. The main outcome measured was the incidence of CCVD. By the end of 2017, 68 921 CCVD events occurred. Men in high LDL-C only, MetS only, and both MetS and high LDL-C groups had higher risks of CCVD. Women in MetS only and both MetS and high LDL-C groups, but not those in high LDL-C only group, had higher risks of CCVD than those in the reference group. The effect of the interaction between the presence of MetS and high LDL-C levels on the primary outcome was found among women ( P for interaction 0.016) but not among men ( P for interaction 0.897). A combination of MetS and LDL-C > 3.4 mmol/L increased the risk of CCVD as compared to MetS or LDL-C > 3.4 mmol/L alone in both men and women. Conclusions: Metabolic syndrome confers an increased risk of CCVD irrespective of sexes; LDL-C > 3.4 mmol/L alone has a greater influence on CCVD occurrence in men than in women. Metabolic syndrome and high LDL-C beget a synergistically detrimental impact on the incidence of CCVD in both men and women. Treatment of dyslipidaemia and metabolic syndrome should be tailored according to patient characteristics.